Evolution of learning folksonomies: social tagging in e-learning repositories. (10th September 2008) - Dahl, Daniel; Vossen, Gottfried
Repositories for learning objects typically offer two different views for the discovery of stored content: search based on keywords and navigation in a context-dependent directory. In the course of the Web 2.0 phenomenon, the social tagging mechanism provides a new way to categorise and organise content. This user-centred approach, generating the so-called folksonomies, is also offering high potential for the context of e-Learning repositories. The paper illustrates how this particular Web 2.0 technique can be exploited within the metadata repository share.loc and the content repository Learnr, both under development at the University of Muenster.